1990
DOI: 10.1113/expphysiol.1990.sp003437
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ovine placental transport of calcium and magnesium by mid‐molecule fragments of human parathyroid hormone‐related protein

Abstract: SUMMARYPerfusion in situ of the placenta of intact or previously parathyroidectomized fetal lambs has been used to assess the ability of three mid-molecule fragments of the human parathyroid hormone-related protein (PTHrP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(83 citation statements)
references
References 4 publications
1
82
0
Order By: Relevance
“…In fetal sheep PTHrP is responsible, at least in part, for maintaining the differential gradient between high fetal serum calcium and that of the maternal circulation (Rodda et al, 1988;Abbas et al, 1989;Care et al, 1990). A midmolecule fragment of PTHrP was suggested to be responsible for placental transport of calcium in sheep (Care et al, 1990), a region which appeared to be present in Sparus saccus through interaction with antibody specific to the midmolecule 50-69 residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fetal sheep PTHrP is responsible, at least in part, for maintaining the differential gradient between high fetal serum calcium and that of the maternal circulation (Rodda et al, 1988;Abbas et al, 1989;Care et al, 1990). A midmolecule fragment of PTHrP was suggested to be responsible for placental transport of calcium in sheep (Care et al, 1990), a region which appeared to be present in Sparus saccus through interaction with antibody specific to the midmolecule 50-69 residues.…”
Section: Discussionmentioning
confidence: 99%
“…In fetal sheep PTHrP is responsible, at least in part, for maintaining the differential gradient between high fetal serum calcium and that of the maternal circulation (Rodda et al, 1988;Abbas et al, 1989;Care et al, 1990). A midmolecule fragment of PTHrP was suggested to be responsible for placental transport of calcium in sheep (Care et al, 1990), a region which appeared to be present in Sparus saccus through interaction with antibody specific to the midmolecule 50-69 residues. Whether PTHrP is also functionally involved in calcium storage or mobilization in the saccus remains to be determined, but it is possible that it may be a factor which helps to maintain calcium concentrations in the CSF within strict limits, because the lumen of the saccus is continuous with that of the third ventricle of the diencephalon of the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…We have no direct evidence that PTHrP of parathyroid origin regulates placental calcium transport in the pig, as it does in the sheep (Rodda et al 1988;Abbas, Pickard, Rodda, Heath, Hammonds, Wood, Caple, Martin & Care, 1989;Care, Abbas, Pickard, Barri, Drinkhill, Findlay, White & Caple, 1990), but PTHrP derived from the placenta itself may have a local action on calcium transport to the fetus. Thyroparathyroidectomy of the ovine fetus, with thyroxine replacements, results in reversal of the placental calcium gradient (Care, Caple, Abbas & Pickard, 1986).…”
Section: Analysesmentioning
confidence: 94%
“…The use of specific antibodies against different epitopes in the molecule has confirmed the heterogeneity. Ovine studies have shown that it is the midregion PTHrp, and not the amino-terminal region, that is functionally active during pregnancy (24). The consideration of this regional selectivity, together with the use of two-site IRMAs, has improved the accuracy of the measurements.…”
Section: Pth and Pthrpmentioning
confidence: 99%